Strengthening Islamic Education Values for Children Through Regular Activities of the Nahdlatul Ulama Female Student Association (IPPNU) in Madura - Nasiruddin, Nasiruddin; Azizah, Kamilatin; Maimun, Maimun (Tebuireng: Journal of Islamic Studies and Society, 2025)
The global spread of technology and Android devices has influenced the social behavior of today's children. Easy access to social media and games has made children reluctant to socialize with society; they are too preoccupied with their gadgets and spend most of their time in the virtual world. Therefore, a forum is needed to educate children on Islamic character development, one of which is through community columns. The purpose of this article is to discuss the strengthening of educational values through regular IPPNU columns in a village, targeting girls in Larangan Tokol Village. The research method used is a case study with data collection in the form of interviews, observations, and documentation. The results of the study describe the implementation of the IPPNU column in Larangan Tokol Village, which was attended by girls in the village and IPPNU administrators as column participants, as well as the Islamic educational values contained in the column activities. It describes the strengthening of Islamic educational values in the column so that Islamic character is formed. The koloman not only serves as a forum for strengthening Islamic educational values but also as a space for strengthening social cohesion from an early age for the children of Larangan Tokol Village.